Ehrlichiosis in a recent kidney transplant recipient: The repellent that did not repel! A case report and literature review of ehrlichiosis in solid organ transplant patients. Issue 4 (5th May 2020) - Masterson, Emily M.; Gupta, Siddhi; Jakharia, Niyati; Peacock, James E.
Abstract: Ehrlichiosis has been infrequently reported in immunosuppressed patients such as solid organ transplants (SOT). We report a case of Ehrlichia chaffeensis infection in an immunosuppressed woman four months after deceased donor kidney transplantation. The diagnosis was confirmed by PCR testing in serum, and the patient responded promptly to treatment with doxycycline. To supplement our Case Report, a literature review encompassing 1995 to present was also performed using PubMed as the search vehicle. Search terms that were utilized include: ehrlichiosis, HME, E chaffeensis, kidney transplant(ation), renal transplant(ation), solid organ transplant(ation), and immunosuppression. The diagnosis of ehrlichiosis can be challenging in SOT patients since ehrlichiosis is not a classic opportunistic infection in SOT. Transplant physicians must have a high clinical suspicion for the diagnosis in patients with an acute febrile illness accompanied by headache, worsening cytopenias, and transaminitis who live in endemic areas, especially if they have tick exposure.